Penerapan Teknik Cognitive Restructuring melalui Konseling Kelompok untuk mengurangi Kecemasan Berbicara di depan Umum Siswa Kelas IX di UPT SPF SMPN 27 Makassar - Yeni Mumtaz Mardiyah (Universitas Negeri Makassar, 2022)
Abstrack. This study aims to determine the effectiveness of using Cognitive Restructuring Techniques in reducing speaking anxiety through group counseling services. This research approach is qualitative. This type of research uses Guidance and Counseling Action Research. The group counseling service carried out includes four stages, namely the initial, transition, core and termination stages and for the Cognitive Restructuring Technique it has 6 stages which generally help students replace negative thoughts that make anxious thoughts more positive. The object of this research is 8 students of 9th grade who experience speaking anxiety. The results showed that the application of Cognitive Restructuring techniques can reduce speaking anxiety which is indicated by changes in student behavior and being able to think of more realistic, rational and positive statements when faced with speaking conditions or situations in front of the other peoples.